Transient erythroblastopenia of childhood in a boy with celiac disease: A case report and review of the literature - Sonia Alexiadou; Anna Papazoglou; Elpis Mantadakis (Elsevier, 2023)
Background: Transient erythroblastopenia of childhood (TEC) is a rare and benign condition characterized by moderate to severe normocytic anemia with low reticulocytes and a spontaneous recovery. Case report: We present a 5-year-old boy with celiac disease who was admitted due to a respiratory tract infection and was diagnosed with TEC along with mild neutropenia. Α bone marrow examination was performed to rule out other causes of hyporegenerative anemia. He recovered spontaneously within 2 months. Conclusion: TEC should be included in the differential diagnosis of any child with normocytic anemia with low reticulocytes. To the best of our knowledge, the present patient is the second case of TEC in a child with celiac disease described to date.